2014
DOI: 10.1371/journal.pone.0092958
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Soil Bacterial Communities in Response to Repeated Application of Manure Containing Sulfadiazine

Abstract: Large amounts of manure have been applied to arable soils as fertilizer worldwide. Manure is often contaminated with veterinary antibiotics which enter the soil together with antibiotic resistant bacteria. However, little information is available regarding the main responders of bacterial communities in soil affected by repeated inputs of antibiotics via manure. In this study, a microcosm experiment was performed with two concentrations of the antibiotic sulfadiazine (SDZ) which were applied together with manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 58 publications
5
79
0
3
Order By: Relevance
“…Ultimately not pooling the samples limited the achievable depth of sequencing per sub-sample as effort was split between 18 individual replicates. It was also hypothesised that sequencing replicate rather than pooled samples would minimise the risk of misinterpreting local spatial variability that has previously been shown to exist and contributing to biogeographical patterns in soil microbial community compositions (Yergeau et al, 2009 Ding et al (2014). As the authors compared applications of manure supplemented with sulfadiazine with applications of unsupplemented manure they concluded that observed differences were attributable to impacts of the antibiotic, and their results are therefore concordant with the findings of the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ultimately not pooling the samples limited the achievable depth of sequencing per sub-sample as effort was split between 18 individual replicates. It was also hypothesised that sequencing replicate rather than pooled samples would minimise the risk of misinterpreting local spatial variability that has previously been shown to exist and contributing to biogeographical patterns in soil microbial community compositions (Yergeau et al, 2009 Ding et al (2014). As the authors compared applications of manure supplemented with sulfadiazine with applications of unsupplemented manure they concluded that observed differences were attributable to impacts of the antibiotic, and their results are therefore concordant with the findings of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…These approaches suffer from an inherent lack of resolution and depth, and it is not possible to evaluate impacts of antibiotic exposure on rarer taxa. To address these issues, the use of techniques such as 16S rRNA gene sequencing for community diversity analysis, as demonstrated by Ding et al (2014), offer the opportunity to gain deeper insights into soil microbial populations. The use, however, of manure either in addition to or as the source of antibiotic residues makes it clearly difficult to disentangle the direct effects of the antibiotics from those of the microbiota present in the manure itself; a limitation to the Ding et al, (2014) study and those mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of the relative abundance of Stenotrophomonas spp. in soils which have been treated by sulfadiazine-amended manure was observed by Ding et al (83).…”
Section: Resultsmentioning
confidence: 76%
“…Functional metagenomic analysis attributed the enrichment of β-lactamases in manure-treated soil to the growth of soil resident genus Pseudomonas sp. harboring β-lactamases, which is commonly found in soil environment and particularly responsive to manure amendment (Ding et al 2014). These findings indicated that amendment of soil with antibiotic-free manure will more likely lead to the proliferation of bacteria carrying β-lactamases possibly originating from the soil samples rather than introduced from manure-derived ARGs, although different β-lactamases were enriched in different soils indicating a soil type specific effect.…”
Section: Temporal Patterns Of Soil Args and Stimulation Of β-Lactam-rmentioning
confidence: 85%